Perbandingan Pengaruh Cahaya Tampak Terhadap Laju Fotosintesis Tumbuhan Hydrilla Verticillata - Harahap, Nur Indah Permatasari; Silvia, Cindy; Fadilla, Audia; Rahma, Alya; Wulandari, Dinda Riris; Fachrizal, Ahmad (CV. ITTC INDONESIA, 2024)
This research aims to provide a comprehensive understanding of the photosynthesis process in plants and how environmental factors such as light can be manipulated to optimize plant productivity. The research method used is a qualitative method with four different treatments. The first treatment involves placing Hydrilla plants and water in the sun. The second treatment involved Hydrilla plants and water placed in a dark room. The third treatment used Hydrilla plants and water placed under LED lights. The fourth treatment used Hydrilla plants and water under incandescent light. The results show that the light reaction will affect the rate of photosynthesis. This research uses Hydrilla verticillata plants, water, LED lights and incandescent lights as the main ingredients. The tools used include a glass funnel, 500 cc glass beaker, wire hook, thread, light fitting and test tube.